VD_FINDINFO Jug / 2025 / 179 vom 20. November 2024 - VD Tribunal cantonal (2024)
CONDAMNATION, EXPULSIONDROIT PÉNAL, DOMMAGE MATÉRIEL, VOLDROIT PÉNAL, ADMISSION DE LA DEMANDE | 139 ch. 1 CP, 144 CP, 186 CP, 22 ad 139 CP, 66b CP, 83 CPP (CH)